Neuromarketing in online education - Kamaladin, D.; Kazybayeva, A. (Journal of Economic Research & Business Administration, 2021)
The article examines the potential of neuromarketing in the system of new high-tech networked pedagogy of the XXI century. The author analyzed the scientific, theoretical and methodological foundations of neuromarketing; identified problems and prospects for the use of neuromarketing in online education. The research methodology includes systemic and interdisciplinary approaches, analysis of scientific and educational literature, including neurophysiological, neuromarketing and psychological and pedagogical research, as well as methods of observation, study and generalization of the pedagogical practice of using neuromarketing technologies. In the course of the study of neuromarketing in online education, the following results were achieved: based on the analysis of scientific publications, the conceptual and terminological apparatus of the new scientific discipline was clarified, indicating its interdisciplinary nature and experimental research content; formulated the concept of neuromarketing as a subsection of neuroeconomics; shows the features and possibilities of combining the methods of “classical” marketing research and neuromarketing research; the definition of neuroeducation is given; identified the problems and prospects of neuromarketing in online education. The author’s main conclusion confirmed the original hypothesis of the study, which is that neuromarketing is not a well-established scientific discipline for its widespread use in online education. This article expands the scientific understanding of neuromarketing in online education, identifies current problems, its limitations and opportunities inherent in neuromarketing as a new applied scientific discipline. Key words: neuromarketing, online education, online learning, neuroscience, neuroeducation.